Maternal obesity and severe preeclampsia among immigrant women: a mediation analysis. (13th November 2019) - Siddiqui, A; Deneux-Tharaux, C; Luton, D; Schmitz, T; Mandelbrot, L; Estellat, C; Howell, E A; Khoshnood, B; Bertille, N; Azria, E
Abstract: Background: Severe preeclampsia is known to be associated with both maternal place of birth and obesity. However, the role of prepregnancy obesity has not been well elucidated on the causal pathway between maternal origin and severe preeclampsia. We aimed to test for and quantify a mediation effect of obesity in this association. Methods: A secondary analysis of the PreCARE prospective French cohort of pregnant women (n = 9, 579). Adjusted path analysis logistic regression models tested for a mediation effect of obesity in the association between maternal place of birth and severe preeclampsia. Adjusted odds ratios and 95% confidence intervals for the total exposure-outcome association and for the direct and indirect/obesity-mediated components were calculated in addition to an estimate of the indirect/obesity-mediated effect. Results: 95 (0.99%) women developed severe preeclampsia: 47.6% were non-European immigrants, 16.3% were born in Sub-Saharan Africa, and 12.6% were obese. Obesity was both associated with Sub-Saharan African place of birth and severe preeclampsia. Women from Sub-Saharan Africa had an increased risk of severe preeclampsia compared to European-born mothers (aOR 2.53, 95% CI 1.39-4.58). The obesity-mediated effect of the association was 18% (aOR 1.18, 95%CI 1.03-1.35). Conclusions: Sub-Saharan African immigrant women have a two-fold higher risk of developing severe preeclampsia as compared to European-born women, one-fifth of which is mediated by prepregnancy obesity. Our results provide estimates of the benefit of decreasing obesity among at-risk women. Key messages: Obesity, a modifiable risk factor, is a target for interventions to prevent severe preeclampsia among immigrant women from Sub-Saharan Africa. Future investigations should focus on better elucidating the role of other modifiable mediators such as interaction with the health care system and quality of prenatal care.